ETHNOMATHEMATICS IN PALM SUGAR PRODUCTION: EXPLORING MATHEMATICAL ACTIVITIES OF ARTISANS AND STUDENTS THROUGH OUTING USING METACOGNITIVE QUESTIONS - Alfiana Syipa Permata; Eko Yulianto; Sinta Verawati Dewi (JME (Journal of Mathematics Education), 2026)
Palm sugar production represents a cultural practice embedded with mathematical concepts. However, these concepts have not been optimally integrated into formal education, resulting in mathematics often being perceived as abstract and disconnected from real life contexts. This study aims to explore the mathematical activities performed by palm sugar artisans and to describe students’ activities in an outing class learning setting employing the problem posing method through a metacognitive questions approach. This research adopted a multi-method design integrating ethnography and phenomenology. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing procedures. The findings identified artisans’ mathematical activities, including counting, measuring, designing, locating, and explaining, in accordance with Bishop’s framework. Additionally, estimating emerged as a newly identified activity that has the potential to enrich ethnomathematics studies. The implementation of outing class learning through a metacognitive questions approach in the context of palm sugar production demonstrated that students actively engaged in counting, measuring, designing, and explaining activities. These results indicate that this approach has strong potential as a meaningful contextual learning resource for developing students’ mathematical activities.